Comparative performance of insulinoma‐associated protein 1 (INSM1) and routine immunohistochemical markers of neuroendocrine differentiation in the diagnosis of endocrine mucin‐producing sweat gland carcinoma. (6th September 2020) - Parra, Ourania; Linos, Konstantinos; Yan, Shaofeng; Lilo, Mohammed; LeBlanc, Robert E.
Abstract: Endocrine mucin‐producing sweat gland carcinoma (EMPSGC) is a rare cutaneous adnexal malignancy with predilection for the eyelids of older adults. It must be distinguished from metastatic adenocarcinomas of extracutaneous origin and from benign adnexal proliferations on partial samples when a solid growth component and mucin production are not evident. Thus, demonstration of neuroendocrine differentiation can help to ensure a correct diagnosis. Insulinoma‐associated protein 1 (INSM1) is a novel neuroendocrine marker that has recently shown greater sensitivity than synaptophysin (SYN) and chromogranin (CHR) in the diagnosis of various neuroendocrine neoplasms. We compared the performance of these three markers across 10 examples of EMPSGC. All EMPSGCs expressed INSM1. Eight of ten were also immunoreactive for SYN; however, INSM1 staining was generally more intense and stained a greater proportion of the tumor cells. CHR staining was weak and focal in most cases. INSM1 staining was present in hidrocystoma‐like components of cystic EMPSGC. These findings suggest that INSM1 may be more sensitive than SYN and CHR and thus valuable for establishing a diagnosis of EMPSGC.